Nancy E. Levine. The Dynamics of Polyandry. Kinship, Domesticity, and Population on the Tibetan Border. Chicago y Londres: The University of Chicago Press, 1988. pp. 309. - A., M. (Estudios de Asia y África, 1997)
-